Molecular characterization, clinical phenotype, and neurological outcome of twelve Palestinian children with beta-ketothiolase deficiency: report of two novel variants in the ACAT1 gene - Imad M. Dweikat; Hamza A. Abdul-Hafez; Alaa Zayed; Moien Kanaan; Hanin Kasem; Rami Bzour (BMC Medical Genomics)
Abstract Background Beta-ketothiolase deficiency (mitochondrial acetoacetyl-CoA thiolase, T2) deficiency (OMIM #203750, *607809) is an autosomal recessive disorder of isoleucine catabolism and ketone body utilization. It is caused by mutations in the ACAT1 gene and characterized by intermittent ketoacidosis episodes triggered by ketogenic stresses, with no clinical symptoms between the episodes. Neurological complications, particularly extrapyramidal signs may occur as sequelae of the ketoacidosis episodes but may also occur without or before any apparent metabolic crisis. T2 deficiency is characterized by the accumulation of isoleucine metabolites, 2methylacetoacetate, 2-methyl-3-hydroxybutyrate, and tiglylglycine, detected in urine organic acids and blood acylcarnitines with or without hypoglycemia. Methods This study presents data from twelve patients with T2 deficiency, diagnosed between 7 months and 22 months of age at two tertiary care centers in Palestine. The clinical, biochemical, molecular genetic data, and neurological outcomes are reviewed. Results We report on twelve patients (6 females and 6 males) from eight families in four different regions of the West Bank and Gaza Strip. All patients were offspring of consanguineous marriages. Ketoacidotic episodes were the predominant manifestations in all patients, and each episode was triggered by either acute gastroenteritis or upper respiratory infections. One patient initially presented with hypotonia and psychomotor delay, later developing a ketoacidotic episode a few months afterward. The characteristic laboratory finding in all patients was the increased urinary excretion of 2-methyl-3-hydroxybutyrate and tiglylglycine. Ten of the twelve patients had favorable outcomes, while two unfortunately passed away at the time of the study. Molecular genetic analysis of the ACAT1 gene was conducted on nine patients from six families, revealing four different variants, two of which were novel. Additionally, a founder mutation was identified in six patients from three families. Conclusions The study underscores the critical role of genetic research in unraveling the complexities of beta-ketothiolase deficiency and related disorders. By identifying haplotype blocks, founder mutations, and novel pathogenic variants, researchers can significantly improve diagnostic precision, enhance genetic counseling, and lay the groundwork for developing targeted therapies. We identified two novel variants and a founder mutation, thereby broadening the genetic spectrum of this rare disease.